Effect of calcium lactate and sucrose on the quality attributes and storage stability of vacuum impregnated jackfruits - Sandianysamy, M. A; Koh, S. P.; Mohd Adzahan, N.; Yusof, N. L. (Rynnye Lyan Resources, 2022)
Vacuum impregnation (VI) is a non-destructive unit operation. VI has been extensively studied with regard to the modification of the physicochemical properties of food products. The VI process allows the introduction of cryoprotectants and preservatives into the intercellular spaces of the plant tissues. Jackfruit is rich in nutrients and due to the increasing demand for minimally processed fruits, jackfruits are cut, packed, and stored before being sold to customers. However, minimal processing causes mechanical injury, leading to an increase in metabolic activity. A way of extending the storage stability of minimally processed jackfruit is required. Thus, the objective of this study is to determine the physicochemical and sensory properties, microbiological quality, and storage stability of vacuum impregnated jackfruit using different texture enhancers, calcium lactate (1.5%) and sucrose (20%) sprayed with fermented jackfruit leaf solution (50%) and stored at 4°C. The samples were stored for 10 days and were analyzed every second day. The firmness and microscopic structure of calcium lactate impregnated samples were significantly higher and more rigid than control and sucrose impregnated samples. Sensory evaluation showed that sucrose impregnated samples had significantly higher scores for taste, aroma, and overall acceptability. Based on visual observation, control samples begin to get mouldy from day 6 while both treated samples had zero mould growth throughout storage. In conclusion, VI extends the shelf life of fresh-cut jackfruit up to 10 days by enhancing the texture and slowing the quality degradation. It is believed that VI treatment provides an alternative method to preserve the food quality of fresh-cut fruits.